(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The results of evaluation of the clinical efficacy of cholecalciferol in the complex treatment of bronchial asthma in children are presented. 60 children with bronchial asthma were examined. All patients were prescribed cholecal ciferol in addition to basic therapy. In all children, the level of the 25(OH)D metabolite was determined in the blood serum. The study of clinical efficacy after treatment showed an increase in the content of vitamin D, in children there was an improvement in the course of the disease: the number of exacerbations per year, the number of night attacks decreased, the length of stay in the hospital was reduced, attacks stopped in a shorter time, the duration of dry and wet cough significantly decreased, it was noted reduction in the duration of shortness of breath, cyanosis of the nasolabial triangle, oral wheezing.